Social networks and natural resource management uncovering the social fabric of environmental governance - Bodin, Örjan 1969-; Prell, Christina (Cambridge University Press, 2011)
"Social Network Analysis (SNA), a quantitative approach to the study of social relations, has recently emerged as a key tool for understanding the governance of natural resources. Bringing together contributions from a range of researchers in the field, this is the first book to fully explore the potential applications of SNA in the context of natural resource management. Topics covered include the role of SNA in stakeholder selection; improving fisheries management and conservation; the effect of social network ties on public satisfaction and agrarian communication networks. Numerous case studies link SNA concepts to the theories underlying natural resource governance, such as social learning, adaptive co-management and social movements theory. Reflecting on the challenges and opportunities associated with this evolving field, this is an ideal resource for students and researchers involved in many areas of natural resource management, environmental biology, sustainability science and sociology".